THE PROBLEM OF INFORMATION SOCIETY VIRTUALIZATION - Любивий, Я. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
In searching of virtualization as the basic characteristics of modern information society are reveals its new lines because continuously innovates this society. Virtual reality becomes inalienable constituent of technological, economical, political, social-organizational and other important social processes. Application of notion of virtual reality expands on such phenomenons as “virtual government”, “virtual bank”, “virtual moneys”, “distance learning”, “virtual politics”, ”virtual economic” and “virtual society” as such. Internet communication takes off some barriers which can appear in personal communication face-to-face and in so way facilitates it. On the other hand, this communication reduce the level of responsibility for the content of it and in so way de-individualizes it. At the same time, internet communication gives to citizens a social support, including internet-discussions and internet-forums on various social, and existential problems. Humanistically oriented mobile communication with distant communicant humanizes also social space around hier-existant communicant. In general, virtual communication promotes to forming not only national, but global movements for justice in various areas of social life and leads to positive changes in society.